2006
DOI: 10.1002/pmic.200600082
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of the dystrophin-deficient MDX diaphragm reveals a drastic increase in the heat shock protein cvHSP

Abstract: Duchenne muscular dystrophy is the most commonly inherited neuromuscular disorder in humans. Although the primary genetic deficiency of dystrophin in X-linked muscular dystrophy is established, it is not well-known how pathophysiological events trigger the actual fibre degeneration. We have therefore performed a DIGE analysis of normal diaphragm muscle versus the severely affected x-linked muscular dystrophy (MDX) diaphragm, which represents an established animal model of dystrophinopathy. Out of 2398 detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
222
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(245 citation statements)
references
References 55 publications
18
222
0
Order By: Relevance
“…Subsequently, 100 ll of extraction buffer (5% formic acid/acetonitrile, 1:2, v/v) was added to the trypsin-treated membranes and gently agitated for 15 min at 37°C. All supernatant fractions were placed into fresh plastic tubes, and peptides were dried down by vacuum centrifugation [9]. Peptides were reconstituted in LC running buffer (0.1% formic acid), centrifuged for 20 min in 22-lm cellulose spin filter tubes to remove any membrane particles, and then aliquoted into LC-MS vials.…”
Section: On-membrane Digestionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, 100 ll of extraction buffer (5% formic acid/acetonitrile, 1:2, v/v) was added to the trypsin-treated membranes and gently agitated for 15 min at 37°C. All supernatant fractions were placed into fresh plastic tubes, and peptides were dried down by vacuum centrifugation [9]. Peptides were reconstituted in LC running buffer (0.1% formic acid), centrifuged for 20 min in 22-lm cellulose spin filter tubes to remove any membrane particles, and then aliquoted into LC-MS vials.…”
Section: On-membrane Digestionmentioning
confidence: 99%
“…The membrane cytoskeletal element consists of an N-terminal actin-binding domain, a central spectrin-like rod domain with proline-rich hinge regions, a cysteine-rich domain, and a C-terminal region containing membrane-binding sites [4]. Although biochemical and cell biological studies have clearly shown that the primary genetic deficiency of dystrophin results in the drastic reduction of the dystrophin-associated glycoprotein complex in X-linked muscular dystrophy [5], recent large-scale proteomic studies have surprisingly not identified dystrophin isoform Dp427 in gel electrophoretically separated muscle preparations [6][7][8][9]. Mass spectrometric approaches also failed to identify integral dystrophin-associated glycoproteins in the accessible total muscle proteome [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides physical and age‐dependent proteome changes, genetic diseases also perturb the normal proteome in muscles 21. Doran and colleagues investigated the effects of the inheritable neuromuscular disorder Duchenne muscular dystrophy using 2D gel electrophoresis and identified 35 at least two‐fold differentially regulated proteins comparing a normal with a dystrophin‐deficient diaphragm 22. Overall, these studies show a remarkable increase in proteins identifiable from skeletal muscle tissue as LC–MS/MS instrumentation advances.…”
Section: Introductionmentioning
confidence: 99%